2020
DOI: 10.3390/ijms21030817
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phagocytosis in the Pro-Inflammatory Response in LDL-Induced Foam Cell Formation; a Transcriptome Analysis

Abstract: Excessive accumulation of lipid inclusions in the arterial wall cells (foam cell formation) caused by modified low-density lipoprotein (LDL) is the earliest and most noticeable manifestation of atherosclerosis. The mechanisms of foam cell formation are not fully understood and can involve altered lipid uptake, impaired lipid metabolism, or both. Recently, we have identified the top 10 master regulators that were involved in the accumulation of cholesterol in cultured macrophages induced by the incubation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
(77 reference statements)
0
24
0
Order By: Relevance
“…Modified LDL particles tend to self-associate, and these self-associates have the size quite analogues to the bacterial and other pathogens. Due to this, the phagocytosis of resident subendothelial cells of the arterial wall can be stimulated ( Orekhov et al, 2020a ).…”
Section: Multiple Modifications Conceptmentioning
confidence: 99%
“…Modified LDL particles tend to self-associate, and these self-associates have the size quite analogues to the bacterial and other pathogens. Due to this, the phagocytosis of resident subendothelial cells of the arterial wall can be stimulated ( Orekhov et al, 2020a ).…”
Section: Multiple Modifications Conceptmentioning
confidence: 99%
“…Several recent studies investigated the role of mollified LDL [53,54]. Native LDL, multiple modified LDL isolated from the blood of atherosclerotic patients, and LDL modified in vitro by desialylation, oxidation, and acetylation were used.…”
Section: Key Genes and Signaling Pathways Involved In Foam Cells Formmentioning
confidence: 99%
“…A recent study revealed the genes encoding inflammatory molecules that were up-regulated upon treatment of macrophages with atherogenic modified LDL and were involved in the development of inflammation [40]. Further knock-down experiments elucidated the relationship between the immune response and cholesterol accumulation [53]. Primary human macrophages were cultured with atherogenic naturally occurring multiply-modified LDL that induced a prominent cholesterol accumulation.…”
Section: Proinflammatory Response As An Inductor Of Intracellular Lipmentioning
confidence: 99%
“…Aggregated modified LDL (agLDL) may cause lipid accumulation in macrophages in two ways. First, it is known that agLDL is recognized by LRP1 and engulfed via phagocytosis [ 12 , 13 ]. Second, as it was shown recently, macrophages may provide degradation of agLDL via lysosomal synapses, which are extracellular hydrolytic compartments [ 14 ].…”
Section: Ldl Uptake: Role Of Receptorsmentioning
confidence: 99%